Energy Expenditure and level of Physical Activity in Universities Academics and Employees (Revista horizonte, 2022)
Physical activity in university workplaces is important for promoting healthy lifestyles and helping to treat chronic diseases. The objective was to determine the differences in energy expenditure, time dedicated to activities and level of physical activity among academics and employees of Universidad Católica del Maule, Chile. The short version of the International Physical Activity Questionnaire was used in a sample of 30 academics and 40 employees aged 23-66. The T-student test for independent samples and the Spearman correlation with a significance of p0.05), nor at the level of physical activity (p=0.89). The results of the study were not statistically significant. The latter is associated with energy expenditure at university (r=0.52, p